1998
DOI: 10.1152/ajpcell.1998.274.2.c500
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of rabbit ClC-2 current expressed in Xenopus oocytes and its contribution to volume regulation

Abstract: In the Xenopus oocyte heterologous expression system, the electrophysiological characteristics of rabbit ClC-2 current and its contribution to volume regulation were examined. Expressed currents on oocytes were recorded with a two-electrode voltage-clamp technique. Oocyte volume was assessed by taking pictures of oocytes with a magnification of ×40. Rabbit ClC-2 currents exhibited inward rectification and had a halide anion permeability sequence of Cl− ≥ Br− ≫ I− ≥ F−. ClC-2 currents were inhibited by 5-nitro-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
92
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(100 citation statements)
references
References 22 publications
8
92
0
Order By: Relevance
“…The authors concluded that gating may be controlled by a Cl Ϫ -binding site accessible only from the exterior and possibly by modification of this site by external protonation (25). ClC-2 activity has been shown to be dependent on acidic pH e (26,27). The regulation of ClC-2 remains, however, puzzling because other (apparently unrelated) mechanisms of activation exist, including cell swelling (see Ref.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that gating may be controlled by a Cl Ϫ -binding site accessible only from the exterior and possibly by modification of this site by external protonation (25). ClC-2 activity has been shown to be dependent on acidic pH e (26,27). The regulation of ClC-2 remains, however, puzzling because other (apparently unrelated) mechanisms of activation exist, including cell swelling (see Ref.…”
Section: Discussionmentioning
confidence: 99%
“…Cell volume was estimated in oocytes by diameter measurements (46). Oocyte diameters were measured using a digital video line measurement system (Ionoptix, Milton, MA) with contrast analysis of digitized image data.…”
Section: Methodsmentioning
confidence: 99%
“…Increased current amplitudes by hypotonicity and EC acidification Thiemann et al, 1992;Grunder et al, 1992;Jordt and Jentsch, 1997;Furukawa et al, 1998;Schwiebert et al, 1998 ClC-3 Guibert et al, 1998 …”
Section: -Ac Dpc Not Didsmentioning
confidence: 99%